Monitoreando la inversión pública: El impacto de MapaRegalías en Colombia - Maximiliano Lauletta; Martín Antonio Rossi; Juan Cruz Vieyra; Diego Arisi (Inter-American Development Bank (IDB), 2019)
– This paper analyzes the impact of MapaRegalías on efficiency in the execution of public investment projects in Colombia. MapaRegalías is an online platform that displays geo-referenced information and data on royalties coming from the extractives sector. The purpose of the platform is to reduce the cost incurred by public officials and citizens when monitoring the use of royalties. The main finding is that after the release of MapaRegalías, public investment projects financed with royalties showed an average increase in efficiency of execution of 7.996 percentage points.
Keywords: D73; O31; H83; H50; L78; O54; 330; digital innovation; efficiency; public investment; transparency